2022
DOI: 10.1021/acs.analchem.1c04627
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Thermal Shift Assay for Fast Construction of Multidimensional Ligand–Target Space

Abstract: Existing thermal shift-based mass spectrometry approaches are able to identify target proteins without chemical modification of the ligand, but they are suffering from complicated workflows with limited throughput. Herein, we present a new thermal shift-based method, termed matrix thermal shift assay (mTSA), for fast deconvolution of ligand-binding targets and binding affinities at the proteome level. In mTSA, a sample matrix, treated horizontally with five different compound concentrations and vertically with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(50 citation statements)
references
References 32 publications
1
35
0
Order By: Relevance
“…This approach provides advantages of reduced instrument time, efforts and cost by overcoming the need for library generation. 26 The data was also searched using library-free mode in DIA-NN which instead generates an in silico library from a protein sequence database (Figure 2, 4) . 36 While their performance have previously been benchmarked and shown unique advantages in large-scale proteomic and phosphoproteomic workflows, they have never been compared for TPP.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This approach provides advantages of reduced instrument time, efforts and cost by overcoming the need for library generation. 26 The data was also searched using library-free mode in DIA-NN which instead generates an in silico library from a protein sequence database (Figure 2, 4) . 36 While their performance have previously been benchmarked and shown unique advantages in large-scale proteomic and phosphoproteomic workflows, they have never been compared for TPP.…”
Section: Resultsmentioning
confidence: 99%
“…25 More recently, it was adopted in a matrix thermal shift assay to detect ligand concentration-dependent stabilisation of proteins, at a single melting temperature. 26 Ruan et al treated K562 lysates with staurosporine, a model widely used for thermal shift assay method evaluation and demonstrated reduction in sample preparation time, cost and effort. By adopting a library-free, DirectDIA approach, they increased throughput and achieved comparable sensitivity for identifying kinase targets to a recent 2D-TPP TMT study.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…159 A recent report found that data independent analysis (DIA) also provides good quantitative precision. 160 Although the melting temperature is a proxy for protein stability, it does not represent an equilibrium measurement of unfolding. Hence, unlike the critical chaotrope concentration in SPROX or other footprinting techniques, melting temperature does not allow direct determination of Δ G unfolding .…”
Section: Methods For Characterizing Protein Damagementioning
confidence: 99%